Anaerobic oxidation of short-chain alkanes in hydrothermal sediments: potential influences on sulfur cycling and microbial diversity - Adams, Melissa M.; Hoarfrost, Adrienne L.; Bose, Arpita; Joye, Samantha B.; Girguis, Peter R. (Frontiers in Microbiology, 2013)
Short-chain alkanes play a substantial role in carbon and sulfur cycling at hydrocarbon-rich environments globally, yet few studies have examined the metabolism of ethane (C2), propane (C3), and butane (C4) in anoxic sediments in contrast to methane (C1). In hydrothermal vent systems, short-chain alkanes are formed over relatively short geological time scales via thermogenic processes and often exist at high concentrations. The sediment-covered hydrothermal vent systems at Middle Valley (MV, Juan de Fuca Ridge) are an ideal site for investigating the anaerobic oxidation of C1-C4 alkanes, given the elevated temperatures and dissolved hydrocarbon species characteristic of these metalliferous sediments. We examined whether MV microbial communities oxidized C1-C4 alkanes under mesophilic to thermophilic sulfate-reducing conditions. Here we present data from discrete temperature (25, 55, and 75 °C) anaerobic batch reactor incubations of MV sediments supplemented with individual alkanes. Co-registered alkane consumption and sulfate reduction (SR) measurements provide clear evidence for C1-C4 alkane oxidation linked to SR over time and across temperatures. In these anaerobic batch reactor sediments, 16S ribosomal RNA pyrosequencing revealed that Deltaproteobacteria, particularly a novel sulfate-reducing lineage, were the likely phylotypes mediating the oxidation of C2-C4 alkanes. Maximum C1-C4 alkane oxidation rates occurred at 55 °C, which reflects the mid-core sediment temperature profile and corroborates previous studies of rate maxima for the anaerobic oxidation of methane (AOM). Of the alkanes investigated, C3 was oxidized at the highest rate over time, then C4, C2, and C1, respectively. The implications of these results are discussed with respect to the potential competition between the anaerobic oxidation of C2-C4 alkanes with AOM for available oxidants and the influence on the fate of C1 derived from these hydrothermal systems.